Towards new approach methodologies for biological therapeutics: a novel model-informed metric to assess immunogenicity risk - Rose, Rachel H.; Shuaib, Aban; Wigbers, Manon; Khalifa, Maryam; Kierzek, Andrzej M.; van der Graaf, Piet H. (Frontiers in Immunology, 2025)
Immunogenicity poses a significant challenge in biotherapeutics development due to the formation of anti-drug antibodies (ADA), which can alter drug pharmacokinetics (PK) and reduce efficacy. However, ADA presence does not always correlate with a clinically relevant reduction in efficacy, or in some cases can be managed by adjusting dosing regimens. Current preclinical strategies focus on predicting the propensity for ADA development, but do not assess the liability for ADA to impact PK. Quantitative systems pharmacology (QSP) models integrate knowledge of biological mechanisms with physiological and drug-specific parameters to predict ADA dynamics and their effect on PK. This study describes recent progress in using QSP models to predict the incidence of immunogenicity and the impact of ADA on PK. We report continued challenges in accurately predicting ADA incidence from available data from experimental and computational methods used in immunogenicity risk assessment. However, across 13 monoclonal antibodies and fusion proteins, the model accurately predicted ADA impact on drug concentration in ten cases, Furthermore, the ADA to drug concentration ratio was identified as a strong predictor of clinically relevant immunogenicity and drug exposure impact.